Using nuclear magnetic resonance proton relaxation to probe the surface chemistry of carbon 2D materials. Issue 13 (5th March 2021) - Marchesini, Sofia; Paton, Keith R.; Brennan, Barry; Turner, Piers; Pollard, Andrew J.
Abstract : Using NMR proton relaxation to rapidly identify surface chemical functionalisation changes of carbon nanomaterials in liquid. Abstract : Nanomaterials exhibit a high surface-area-to-mass ratio, making surface properties key to optimising product performance. However, characterising surfaces at the nanoscale is difficult to achieve, especially as nanomaterials are often in liquid dispersions. Herein, we demonstrate the use of nuclear magnetic resonance proton relaxation for rapid characterisation of the surface chemistry of graphitic materials.